Dasar Teologis bagi Implementasi Etos Global dalam Perspektif Kristen - Guidelbertus Tanga; Georg Ludwig Kirchberger (Jurnal Ledalero, 2022)
Abstract: This article departs from the declaration of the global ethos, which was declared by the Parliament of World Religions in Chicago, in 1993. It expresses the belief that many people can agree with the principles and values stated in it. After that the question is raised how this ethos can be implemented. To answer this question, the article follows the suggestion of Hans Küng, the initiator of the global ethos, that every religion should investigate its traditions, in order to find a deeper understanding of these values and the motivations that can help to develop attitudes that support these values. So in this article a description is made of the Christian tradition, of God’s law and the essence of sin as a force and as human action. Then the whole history of salvation is described as an attempt from God to introduce himself with His true face as God who wants humans to have life in all the abundance, which therefore can be trusted as the basis and guarantor of human life and existence. Finally follows the conclusion that this truth about God needs to be proclaimed by the Christian Church, so that in response to God’s actions and works, humans can become able to let go selfishness and compulsion to seek as much wealth and power for themselves as possible. So people can become capable of practicing the values as stated in the declaration of the global ethos.Keywords: global ethos, parliament of world religions, God’s law, core power of sin, Paul’s theology, justification, covenant theology.